The casein kinase 2 inhibitor, CX-4945, as an anti-cancer drug in treatment of human hematological malignancies - Chon, Hae J.; Bae, Kyoung J.; Lee, Yura; Kim, Jiyeon (Frontiers in Pharmacology, 2015)
The casein kinase 2 (CK2) protein kinase is a pro-survival kinase and therapeutic target in treatment of various human cancers. CK2 overexpression has been demonstrated in hematological malignancies, including chronic lymphocytic leukemia, chronic myeloid leukemia, acute lymphoblastic leukemia, acute myeloid leukemia, and multiple myeloma. CX-4945, also known as Silmitasertib, is an orally administered, highly specific, ATP-competitive inhibitor of CK2. CX-4945 induces cytotoxicity and apoptosis and is currently being evaluated in clinical trials for treatment of many cancer types. In the past two years, the focus on the therapeutic potential of CX-4945 has shifted from solid tumors to hematological malignancies. CX-4945 exerts anti-proliferative effects in hematological tumors by downregulating CK2 expression and suppressing activation of CK2-mediated PI3K/Akt/mTOR signaling pathways. Furthermore, combination of CX-4945 with other inhibitors yielded synergistic effects in cell death induction. These new findings demonstrate that CK2 overexpression contributes to blood cancer cell survival and resistance to chemotherapy. Combinatorial use of CX-4945 is a promising therapeutic tool for treatment of hematological malignancies.